KOMENTAR UJARAN KEBENCIAN KASUS PENANGKAPAN NURDIN ABDULLAH DI AKUN TWITTER CNN INDONESIA KAJIAN LINGUISTIK FORENSIK - Pangestuti, Manesti (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
Nowadays, the use of social media is a necessity to interact, socialize, communicate, and access various information, but in this use, there are still many cases of abuse such as carrying out prohibited actions. Actions on electronic social media have been regulated by the Information and Electronic Transaction Law (UU ITE) so that every action taken will be judged by applicable law. Hate speech in the comments column for electronic social media often occurs but there are still many users who do not understand the law. The purpose of this study is to present examples of hate speech in the comments column of electronic social media, namely Twitter in one of the CNN Indonesia account posts related to the case of Nurdin Abdullah's arrest. The theory used is a forensic linguistic study to find out the study of the language of the comments and then linked it with the applicable law. The method used is descriptive qualitative analysis with 5 comments. The results obtained show that the comments are hate speech which is included in the criminal act of defamation and can be punished by the ITE Law article 27 paragraph (3) regarding defamation in electronic mass media and the KUHP article 310 paragraph (2) related to defamation. Written.